Analisa Pengaruh Citra Destinasi, Loyalitas Destinasi, Kualitas Destinasi terhadap Niat Berkunjung Ke Kota Batam - Kurniawan, Robby; Siaurence, Junkeezy (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The tourism industry has an important role in the economy of a country, therefore the country strives to provide the best service for all tourists. The state seeks to build a destination image, the quality of a destination, and loyalty to tourists in order to build the attractiveness of a destination so that tourists have the intention to visit a destination. Batam City is in the Riau Islands province, Indonesia. Batam is one of the tourist destinations in Indonesia which is visited by many tourists. Visiting intention is defined as someone's intention to travel or visit a place. Intention to visit is the result of a mental process that leads to action and can change a person's motivation into behavior. Destination image is an important factor in tourist quality, because the dimensions and elements that make up a destination image can vary greatly, it requires a decision-making process, destination preferences, satisfaction and future behavioral intentions, contextualized understanding to understand the role of destination image in a destination. certain. Loyalty is a deep commitment from customers to continue buying a product or service again in the future. Developing loyalty towards customers has become an important marketing strategy because utilizing existing customers, loyal customers not only represent a source of stable income. The quality of a destination is important for tourists who try to determine their own production standards for products and services. This is very important because it has a positive impact on the attitudes and behavior of tourists in the future regarding their intention to visit a tourism destination. The quality of each tourist is different so it must be adjusted to certain criteria or standards.